Environmental stress prevention in pediatric wards by design / Sharona Ghorbani - Ghorbani, Sharona (2014)
Quantitative and qualitative research methods were used to explore the relationship between physical environmental factors in pediatric wards and their influence on healing process. This study is in term of improving the physical environment of children care spaces which affects indirectly the whole process of healing in hospitals or all the other care spaces when it prevents the environmental stress. It puts forward a literature of environment design dynamic movements on children care spaces design which have been done previously by designers and researchers. The physical environmental factors of pediatric wards have healing influence on children healing and how mental well-being of inpatient children could be enhanced through proper realization during the hospitalization. To achieve this purpose, the objectives of this study were to study about physical environment in current children’s care spaces and to investigate about the children’s preference on physical environment of wards and causes of problem among patients in the ward. This study could help to improve the quality of children care spaces by applying some changes in the existing design. The propose of this research was to gather through the previous researches and my own information from findings and observation in process of my research methodology to find a better understanding about physical environmental factors of children’s care spaces and how to make it more homelike and less stressful. That could help to increase the knowledge of existing and future designers and researchers accordingly. As a result of this research, design of the interior in children wards can make the hospital environment more patients friendly and home-like to optimize the result of treatment and healing process. It could only happen by applying proper design consideration to deliver patient’s needs. The research confirmed and proved that the physical environment at the existing care spaces have mostly weakness to be improved or issues that must be added to their interior design to meet the standard requirements of healing environment as exposed by past researches in literature review. The research pointed on low satisfaction level of users and tried to collect preferences of parents and visitors for a brighter future of pediatric wards environment.